BLENDED LEARNING IN HIGHER EDUCATION - Qilichova Zarifa Khayrullo qizi (Bright Mind Publishing, 2025)
Mixed education in higher education is recognized as one of the most relevant and effective areas of the modern educational system. This form of education is based on harmonizing traditional classes and audience training with online educational tools. As a result, students gain more independence in the course of their studies and have the opportunity to study their knowledge more deeply and more broadly. Mixed education allows students not only to acquire new knowledge, but also to apply them in practice, develop critical thinking and creative approaches.
Keywords: Education, ability, critical thinking, creative activity, knowledge, skills, audience training, courses, abstracts, resources.